Distribution of Fish Target Strength in Malang Rapat Seawater of Bintan Island, Kepulauan Riau Province - Andi Yaodi Nurani Yamin; Henry M Manik; Sri Pujiyati (Journal of Applied Geospatial Information, 2020)
Malang Rapat is an area located in east Bintan Island. As a part of coastal communities, fisheries were the primary sector for public revenue in Malang Rapat. A qualified method is needed to determine the abundance and distribution of fish were required. Hydroacoustic technology is one method to solve this problem. This research aimed was to determine the value of fish target strength and to determine the pattern of fish distribution behavior in Malang Rapat, Kepulauan Riau Province, on September 23 and 24, 2016, using scientific echosounder Simrad EK15. The result indicated that fish target strength in Malang Rapat was -60 dB to -42 dB. This value was useful to estimate the length of fish ranged from 3 cm to 31 cm. The highest mean target strength based on depth was -48 dB at 10 m in the daytime and -52 dB at 3 m in the nighttime. The abundance of fish was found at night, precisely 3 meters from the surface of the water. The highest frequency appearance target strength range from -60 dB to -58 dB with 3.94 to 4.95 cm estimated fish length.